Impact of ABC single nucleotide polymorphisms upon the efficacy and toxicity of induction chemotherapy in acute myeloid leukemia. Issue 5 (4th May 2017) - Megías-Vericat, Juan Eduardo; Montesinos, Pau; Herrero, María José; Moscardó, Federico; Bosó, Virginia; Rojas, Luis; Martínez-Cuadrón, David; Hervás, David; Boluda, Blanca; García-Robles, Ana; Rodríguez-Veiga, Rebeca; Martín-Cerezuela, María; et al.
Abstract: Anthracycline uptake could be affected by efflux pumps of the ABC family. The influence of 7 SNPs of ABC genes was evaluated in 225 adult de novo acute myeloid leukemia (AML) patients. After multivariate logistic regression there were no significant differences in complete remission, though induction death was associated to ABCB1 triple variant haplotype ( p  = .020). The ABCB1 triple variant haplotype was related to higher nephrotoxicity ( p  = .016), as well as this haplotype and the variant allele of ABCB1 rs1128503, rs2032582 to hepatotoxicity ( p  = .001; p  = .049; p  < .001). Furthermore, the variant allele of ABCC1 rs4148350 was related to severe hepatotoxicity ( p  = .044), and the variant allele of ABCG2 rs2231142 was associated to greater cardiac ( p  = .004) and lung toxicities ( p  = .038). Delayed time to neutropenia recovery was observed with ABCB1 rs2032582 variant ( p  = .047). This study shows the impact of ABC polymorphisms in AML chemotherapy safety. Further prospective studies with larger population are needed to validate these associations.